2016
DOI: 10.1039/c6ta08850c
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide modified hydrate salt hydrogels: form-stable phase change materials for smart thermal management

Abstract: The adjustment of phase transition behaviors based on the special interaction of GO and PAAAM with hydrate salt PCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…Thes upercooling degrees of EHS,E HS/PAAAM, and HTC-EHS/ PA AAM are calculated and presented in Figure 8( 16.3, 14.6, and 7.9 8C). TheH TC-EHS/PAAAM composite shows the narrowest supercoolingd egree,a nd this means that the 1.4 wt %d oping of HTC can effectively adjust the supercooling effect of EHS.C ompared with the previous research, [36] 2wt% content of graphene oxide (GO) was required to achieve the same effect, for which the melting enthalpyo fG O-EHS/PAAAM was 200.3 Jg À1 and the supercooling degree was 8.0 8C. In comparison,H TC-EHS/PAAAMw ith lower HTC content showedb etter performance in the thermal properties of form-stable PCMs.T he reason may be different morphologies of GO and HTC,w hich exhibit flake structure and spherical structure,r espectively.…”
Section: Thermalproperties Of Htc-ehs/paaammentioning
confidence: 61%
See 2 more Smart Citations
“…Thes upercooling degrees of EHS,E HS/PAAAM, and HTC-EHS/ PA AAM are calculated and presented in Figure 8( 16.3, 14.6, and 7.9 8C). TheH TC-EHS/PAAAM composite shows the narrowest supercoolingd egree,a nd this means that the 1.4 wt %d oping of HTC can effectively adjust the supercooling effect of EHS.C ompared with the previous research, [36] 2wt% content of graphene oxide (GO) was required to achieve the same effect, for which the melting enthalpyo fG O-EHS/PAAAM was 200.3 Jg À1 and the supercooling degree was 8.0 8C. In comparison,H TC-EHS/PAAAMw ith lower HTC content showedb etter performance in the thermal properties of form-stable PCMs.T he reason may be different morphologies of GO and HTC,w hich exhibit flake structure and spherical structure,r espectively.…”
Section: Thermalproperties Of Htc-ehs/paaammentioning
confidence: 61%
“…As an interestingp henomenon, on the right-hands ide of Figure 4, the original characteristic absorption peak of C=Oi np ure PA AAM was observed at 1554 cm À1 , [56] when PA AAM was mixed together with EHSt op roduce EHS/PAAAM, the absorption peak of C=Os hifted from 1554 to 1576 cm À1 ;h owever, with the addition of HTC in HTC-EHS/PAAAM, the absorption peak position of C=Oi nP AAAMc hanged again, moving to 1560 cm À1 .C ompared with the peak position in EHS/PAAAM, itm oved closer to the original position in pure PA AAM. Known from this phenomenon and the above-mentioned previous research, [32][33][34][35][36] it is inferred that the additiono fH TC could partly protect PA AAM form the influence of EHS;i no ther words,w ith the addition of HTC the influence of PA AAM on EHS could be reduced,s ot hat EHS could betterm aintain its original thermal storage function.…”
Section: Structural Characterizationmentioning
confidence: 63%
See 1 more Smart Citation
“…% EG was known as the most suitable selection. Liu [65] combined graphene oxide-modified hydrate salt with poly copolymer hydrogel. The results indicated that the obtained composite was a promising material for achieving further Porous materials like carbon foam, diatomite, expanded graphite and expanded perlite used as supporting materials can also effectively overcome leakage, phase separation and corrosion problems of PCMs.…”
Section: Phase Separation Of Salt Hydratesmentioning
confidence: 99%
“…Ultimately, the system with 3 wt % EG was known as the most suitable selection. Liu [65] combined graphene oxide-modified hydrate salt with poly copolymer hydrogel. The results indicated that the obtained composite was a promising material for achieving further phase transition behavior targets, which can be used for thermal storage under a wide scope of ambient temperatures.…”
Section: Phase Separation Of Salt Hydratesmentioning
confidence: 99%